DESIGN OF TEACHING MATERIALS WITH PYTHON-ASSISTED NUMERICAL METHODS TO DEVELOP STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY - Kristy Agustina; Abdul Baist (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to design and examine the feasibility of Python-assisted numerical methods teaching materials in the form of a problem-based learning module intended to support the development of studentsâ€™ mathematical creative thinking abilities. The research adopts a research and development (R&D) approach using the ADDIE model and is limited to the Analysis, Design, and Development phases. In the analysis phase, curriculum documents and numerical methods course syllabi were reviewed and interviews were conducted with lecturers to identify course learning outcomes, key indicators, and studentsâ€™ difficulties related to numerical methods and mathematical creative thinking. In the design phase, the structure and components of the module were specified, including orientation sections, explanations of concepts and procedures, worked examples, practice exercises, problem-based tasks integrating Python programming, evaluations, and answer keys, all aligned with indicators of mathematical creative thinking. In the development phase, a draft of the module was produced and subjected to expert validation by media, content, and education experts using a Likert-scale instrument, followed by a small-group trial with students. The expert validation results showed an average score of 75.26% in the â€œStrongâ€ category, while student responses reached an average of 92.3% in the â€œVery Strongâ€ category, indicating that the module is valid and highly practical for numerical methods learning. These findings suggest that the Python-assisted, problem-based numerical methods module is feasible for use in lectures and has promising potential to support the development of studentsâ€™ mathematical creative thinking abilities, which should be further investigated through subsequent experimental or quasi-experimental studies that directly measure learning outcomes and creative thinking.